Recent advances in understanding adverse effects associated with drugs targeting the serotonin receptor, 5-HT GPCR - Jamu, Isabella Marie; Okamoto, Haruko (Frontiers in Global Women's Health, 2022)
It has been acknowledged that more women suffer from adverse effects of drugs than men globally. A group of drugs targeting serotonin [5-hydroxytryptamine] (5-HT) binding G-protein-coupled receptors (GPCRs) have been reported to preferentially affect women more than men, causing adverse effects such as breast cancer and infertility. 5-HT GPCR-targeted drugs in the central nervous system (CNS) manage psychiatric conditions, such as depression or bipolar and in the peripheral nervous system (PNS) treat migraines. Physiological characteristics such as specific types of hormones, higher body fat density and smaller body mass in women result in disparities in pharmacodynamics of drugs, thus explaining sex-related differences in the observed adverse effects. In this review, we discuss the side effects of drugs targeting 5-HT GPCRs based on serotonin’s roles in the CNS and PNS. We have systematically reviewed adverse effects of drugs targeting 5-HT GPCR using information from the Food and Drug Administration and European Medicines Agency. Further information on drug side effects and receptor targets was acquired from the SIDER and DrugBank databases, respectively. These drugs bind to 5-HT GPCRs in the CNS, namely the brain, and PNS such as breasts, ovaries and testes, potentially causing side effects within these areas. Oestrogen affects both the biosynthesis of 5-HT and the densities of 5-HT GPCRs in given tissues and cells. 5-HT GPCR-targeting drugs perturb this process. This is likely a reason why women are experiencing more adverse effects than men due to their periodic increase and the relatively high concentrations of oestrogen in women and, thus a greater incidence of the oestrogen-mediated 5-HT system interference. In addition, women have a lower concentration of serotonin relative to men and also have a relatively faster rate of serotonin metabolism which might be contributing to the former. We discuss potential approaches that could mitigate at least some of the adverse effects experienced by women taking the 5-HT GPCR-targeting drugs.